Association between markers of emphysema and more severe chronic obstructive pulmonary disease. Issue 12 (12th June 2006) - Boschetto, P; Quintavalle, S; Zeni, E; Leprotti, S; Potena, A; Ballerin, L; Papi, A; Palladini, G; Luisetti, M; Annovazzi, L; Iadarola, P; De Rosa, E; et al.
Abstract : Background: The predominant emphysema phenotype is associated with more severe airflow limitation in patients with chronic obstructive pulmonary disease (COPD). A study was undertaken to investigate whether COPD patients, with or without emphysema quantitatively confirmed by high resolution computed tomography (HRCT), have different COPD severity as assessed by the BODE index (body mass index, airflow obstruction, dyspnoea, exercise performance) and inspiratory capacity to total lung capacity ratio (IC/TLC), and by different biological markers of lung parenchymal destruction. Methods: Twenty six outpatients with COPD and eight healthy non-smokers were examined. Each subject underwent HRCT scanning, pulmonary function tests, cell counts, and measurements of neutrophil elastase, matrix metalloproteinase (MMP)-9 and tissue inhibitor of metalloproteinase (TIMP)-1 in induced sputum, as well as measurement of desmosine, a marker of elastin degradation in urine, plasma and sputum. Results: Patients with HRCT confirmed emphysema had a higher BODE index and lower IC/TLC ratio than subjects without HRCT confirmed emphysema and controls. Forced expiratory volume in 1 second (FEV1 ), FEV1 /forced vital capacity ratio, and carbon monoxide transfer coefficient were lower, whereas the number of eosinophils, MMP-9, and the MMP-9/TIMP-1 ratio in sputum were higher in patients with emphysema. In COPD patients the number of sputum eosinophils was the biological variable that correlated positively with the HRCT score of emphysema (p = 0.04). Conclusions: These results suggest that COPD associated with HRCT confirmed emphysema is characterised by more severe lung function impairment, more intense airway inflammation and, possibly, more serious systemic dysfunction than COPD not associated with HRCT confirmed emphysema.